Liquefaction risks on bulk cargoes carrying unamended & amended Gebeng bauxite in accordance to International Maritime Solid Bulk Cargoes (IMSBC) code - Muhammad Fat-Hi Al Juwaini, Pahrol (2017)
Improving aggregate formation and stability of bauxite is essential in order to understanding the risk of liquefaction in bulk cargoes. Effects of gypsum and vermicompost on related chemical and physical conditions of bauxite residue were studied in a laboratory incubation experiment. Addition of gypsum at 2% and 4% w/w reduced pH and exchangeable sodium percentage, whilst increasing exchangeable calcium content. Addition of vermicompost reduced bulk density, whilst significantly increasing porosity and total organic carbon. Vermicompost had a positive effect on the formation and stabilization of water-stable aggregates in the residue, whilst gypsum was more beneficial to silt-sized micro aggregate flocculation. Amendments also enhanced the erosion resistance of bauxite residue. Furthermore, wet sieving using the modified Le Bissonnais’ (LB) method revealed that in comparison to differential clay swelling and mechanical breakdown, slaking was the major disaggregation mechanism of residue aggregates. The combination of gypsum and vermicompost converted the residue from a sheet-like structure to a granular macro aggregated structure, whilst converting micro aggregates from a grain to a granular or prismatic structure. The findings of this work suggest that application of gypsum and vermicompost to bauxite residue may directly influence aggregate size distribution and its micromorphology, resulting in the improvement of both aggregate stability and structure to reduce liquefaction risk.